Assessment of the Financial Status of Parents as a Correlate of Students’ Academic Achievement in English Language in Public Secondary Schools in Uyo Local Government Area - Aniekan NYARKS, Ph.D (Zien Journals, 2022)
The study sought to find out how the financial status of parents relate to academic achievement of the students in English language. Correlational survey design was adopted for the study. The study was carried out in selected public secondary schools in Uyo Local Government Area of Akwa Ibom State. The population of this study comprised senior secondary two students in Uyo Local Government Area. There are 14 public secondary schools in Uyo Local Government Area and the estimated population of SS2 students was 3162. Simple random sampling technique was used to select eight public secondary schools where 303 SS 2 students were randomly selected for the study. The instrument used in this study for data collection was a questionnaire titled "Students Factors Questionnaire (SFQ)". The instrument was vetted and content validated by the researcher’s supervisor and two lecturers who are experts in language education in the University of Uyo to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.97, and this was high enough to justify the use of the instrument. The data were analyzed using t-test and Pearson Product Moment Correlation statistics analysis. The test for significance was done at 0.05 alpha levels. the study found out that parent with lucrative occupations provide sufficiently for their children academic pursuit. This will motivate their wards academic achievement. But student whose parents have low occupation standing find it difficult to achieve academic excellence. The study concluded that students/learners whose parents are rich and provide most of their children’s requisitions in schools would perform academically better than students/learners whose parents are poor. Financial capacities enhance academic achievement. One of the recommendations made in the study was that teachers should dialogue with low-income parents to look for additional good business to augment their earnings in order to provide minimum learning/study materials to their children.
Keywords: Financial Status; Parents; Students’; Academic Achievement